Mathematical model for definition of distribution centers in logistics supply networks for oil platforms - Gomes, Thiara Cezana; Rosa, Rodrigo de Alvarenga (Brazilian Journal of Production Engineering, 2022)
Among the objectives of supply chain management is the availability of products and services in the correct quantity, place and time. For this, the location of the facilities in the network of suppliers, warehouses and customers is very relevant. especially when it comes to a country with a large territorial extension like Brazil. This becomes even more relevant when logistics networks deal with the issue of supplies with high added value, as in the case of oil platforms. Thus, this paper seeks to develop a mathematical model based on the Facility Location Problem of Distribution Centers (DC) for a better configuration of the supply logistics network of oil exploration and production platforms. Eight different scenarios were created and run in the CPLEX 12.6 solver. Transport costs represent 52.0% to 69.0% of the percentage of costs involved in the elaboration of the logistics network. The greatest profitability was demonstrated when larger trucks were used at the expense of small capacity trucks. In 50.0% of the cases, only two DC were allocated and the average occupancy of the allocated DC was 72.0%.